INNOVATIVE TRENDS OF FINANCIAL ENGINEERING TO THE WAY OF DIGITAL ECONOMY - Світлана Халатур; Олена Довгаль; Олександр Карамушка; Лариса Бровко; Оксана Водолазська (Фінансово-кредитна діяльність: проблеми теорії та практики)
The modern world is undergoing rapid and profound changes driven by the rapid development of digital technologies that are affecting all aspects of economic life. The transition to a digital economy is becoming increasingly evident, creating new opportunities and challenges for various sectors, including the financial industry. Financial engineering, as a discipline that combines finance, mathematics, statistics, and information technology, is a key tool in shaping modern financial strategies and products. In this context, it is important to explore the innovative trends that determine the development of financial engineering in the digital economy. This article aims to explore the latest trends in financial engineering that contribute to the transition to the digital economy. Particular attention will be paid to analyzing the impact of digital financial instruments on global markets and the role of financial institutions in the new digital environment. The study of these aspects will not only help to understand the current transformation processes but also to predict further directions of financial engineering development and its impact on the digital economy. This, in turn, will help to develop more effective strategies for managing financial risks and opportunities in the new environment, ensuring the sustainable development of the financial system and the economy as a whole. The digital economy is fundamentally changing the way financial markets and businesses operate. This article explores the main innovative trends in financial engineering that contribute to the emergence and development of the digital economy. Also, the prospects and challenges associated with the implementation of these technologies are discussed.